Analysis of land surface parameters and turbulence characteristics over the Tibetan Plateau and surrounding region. Issue 16 (31st August 2016) - Wang, Yinjun; Xu, Xiangde; Liu, Huizhi; Li, Yueqing; Li, Yaohui; Hu, Zeyong; Gao, Xiaoqing; Ma, Yaoming; Sun, Jihua; Lenschow, Donald H.; Zhong, Shiyuan; Zhou, Mingyu; et al.
Abstract: Based on the results from 11 flux sites during the third Tibetan Plateau (TP) Experiment (TIPEX III), land surface parameters and the turbulence characteristics of the atmospheric surface layer over the TP and surrounding region are analyzed. Monin‐Obukhov similarity theory has been used to calculate the aerodynamic roughness length z 0 m and the excess resistance to heat transfer kB − 1  = ln( z 0 m / z 0 h ), and the factors that cause variations of z 0 m and kB − 1 are investigated. The main drivers for the diurnal variations of surface albedo ( α ) at different sites are solar elevation, solar radiation, and soil moisture. The eddy correlation method is utilized to inversely calculate bulk transfer coefficients for momentum ( CD ) and heat ( CH ) at different sites. The relationships between CD and CH and the wind speed at 10 m follow a power law for unstable stratification. For stable stratification, both CD and CH increase with increasing wind speed when wind speed is less than 5 m/s. Diurnal variations of turbulent fluxes are compared at different sites, and the relationships between turbulent fluxes and other variables are analyzed. Wind speed variance normalized by the friction velocity ( σ u / u *,   σ v / u *,   σ w / u * ) for neutral stratification ( C u 1, C v 1, C w 1 ), and temperature and humidity variance normalized by a temperature and humidity scale ( σ T / T *,   σ q / q * ) under free convection ( z / L  < −0.1) ( CT, Cq ) are fitted with similarity relations. The differences in similarity constants ( C u 1, C v 1, C w 1, CT, Cq ) at different sites are discussed. For stable stratification, cases are divided into weakly stable conditions and intermittent turbulence, and the critical values for these two states are determined. Shear and buoyancy terms in the turbulence kinetic energy equation for different stratifications are analyzed. Key Points: A multiscale network of land‐air flux comprehensive observation sites has been implemented for the first time on the TP in TIPEX III Here we place great emphasis on land surface parameters and turbulence characteristics on the TP and surrounding region